2022
DOI: 10.3390/ijms23147890
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression of MfWRKY7 of Resurrection Plant Myrothamnus flabellifolia Enhances Salt and Drought Tolerance in Arabidopsis

Abstract: Drought and salinity have become major environmental problems that affect the production of agriculture, forestry and horticulture. The identification of stress-tolerant genes from plants adaptive to harsh environments might be a feasible strategy for plant genetic improvement to address the challenges brought by global climate changes. In this study, a dehydration-upregulated gene MfWRKY7 of resurrection Plant Myrothamnus flabellifolia, encoding a group IId WRKY transcription factor, was cloned and characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…In addition, a series of antioxidant systems, including SOD, CAT, and POD, have been evolved in plants to mitigate ROS-induced damages. A growing number of studies have demonstrated that WRKYs enhance drought tolerance by reducing MDA content or increasing antioxidant enzyme activity in transgenic plants [39,43,50]. Our data show that MDA content is signi cantly decreased, and SOD, CAT, and POD activities are evidently enhanced in McWRKY57-like OE plants after drought treatment (Fig.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In addition, a series of antioxidant systems, including SOD, CAT, and POD, have been evolved in plants to mitigate ROS-induced damages. A growing number of studies have demonstrated that WRKYs enhance drought tolerance by reducing MDA content or increasing antioxidant enzyme activity in transgenic plants [39,43,50]. Our data show that MDA content is signi cantly decreased, and SOD, CAT, and POD activities are evidently enhanced in McWRKY57-like OE plants after drought treatment (Fig.…”
Section: Discussionmentioning
confidence: 50%
“…Similarly, we found that McWRKY57-like plays a positive role in McWRKY57-likeoverexpressing transgenic Arabidopsis plants. The size and architecture of the root system are key factors affecting the ability of plants to access water and nutrients, and root length is an important indicator of plant drought tolerance [42][43][44]. We found that, although the root growth of WT and McWRKY57-like OE transgenic seedlings is not signi cantly different, under drought conditions, the root length is signi cantly longer in McWRKY57-like OE transgenic seedlings than in WT seedlings (Fig.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Among them, proline not only acts as an osmolyte but also functions as a potent antioxidant and programmed cell death inhibitor, making it one of the most important indicators of plant drought tolerance [ 47 , 48 ]. Soluble sugars and soluble proteins are also important osmoregulatory substances that maintain turgor pressure and macromolecular structure and function, thereby improving plant drought tolerance [ 43 , 44 ]. In this study, osmotic stresses significantly enhance McWRKY57-like expression, and the contents of these three osmolytes are more markedly increased in McWRKY57-like OE plants than in WT under drought treatment (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a series of antioxidant systems, including SOD, CAT, and POD, have been evolved in plants to mitigate ROS-induced damages. A growing number of studies have demonstrated that WRKYs enhance drought tolerance by reducing MDA content or increasing antioxidant enzyme activity in transgenic plants [ 39 , 43 , 50 ]. Our data show that MDA content is significantly decreased, and SOD, CAT, and POD activities are evidently enhanced in McWRKY57-like OE plants compared with WT plants after drought treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%